The Fourth Industrial Revolution, Aging Workers, Older Learners, and Lifelong Learning - Chaewon Yang (Adult Education Research Conference, 2019)
This session aims to review literature related to the technological development of the Fourth Industrial Revolution, aging, and adult education and discuss how adult education can help adult learners and older workers to create opportunities for technological developments in the Fourth Industrial Revolution.
Keywords: aging; older workers; 4th Industrial Revolution